2017
DOI: 10.1016/j.pmedr.2017.10.011
|View full text |Cite
|
Sign up to set email alerts
|

Associations of lifetime walking and weight bearing exercise with accelerometer-measured high impact physical activity in later life

Abstract: High impact physical activity (PA) is thought to benefit bone. We examined associations of lifetime walking and weight bearing exercise with accelerometer-measured high impact and overall PA in later life. Data were from 848 participants (66.2% female, mean age = 72.4 years) from the Cohort for Skeletal Health in Bristol and Avon, Hertfordshire Cohort Study and MRC National Survey of Health and Development. Acceleration peaks from seven-day hip-worn accelerometer recordings were used to derive counts of high i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…Our classifiers were able to accurately detect bouts of walking and jogging, which are important activities for several health outcomes [ 51 ] including skeletal health. Clinical trials have shown that walking improves femoral neck bone mineral density [ 52 ], and population studies have found that participation in walking since age 50 is associated with higher levels of osteogenic physical activities in older age [ 53 ]. Similarly, an analysis of UK Biobank data found that accumulating 1–2 min/day or high intensity PA equivalent to slow jogging in postmenopausal women was associated with better bone health [ 54 ].…”
Section: Discussionmentioning
confidence: 99%
“…Our classifiers were able to accurately detect bouts of walking and jogging, which are important activities for several health outcomes [ 51 ] including skeletal health. Clinical trials have shown that walking improves femoral neck bone mineral density [ 52 ], and population studies have found that participation in walking since age 50 is associated with higher levels of osteogenic physical activities in older age [ 53 ]. Similarly, an analysis of UK Biobank data found that accumulating 1–2 min/day or high intensity PA equivalent to slow jogging in postmenopausal women was associated with better bone health [ 54 ].…”
Section: Discussionmentioning
confidence: 99%
“…Until accelerometers were developed, questionnaires were used to estimate the degree of loading to the skeleton through quantification of PA [ 4 , 5 ]. This proxy measure of mechanical loading was often obtained using self-reported PA in older adults [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…The positive benefits of differing physical activities to bone have been widely investigated. Elhakeem and colleagues findings suggested that walking and weight bearing exercise, such as tennis and dancing, may be important for better skeletal health in older age [ 5 ]. The benefit of resistance training on skeletal health has also been demonstrated.…”
Section: Introductionmentioning
confidence: 99%